STUDI TENTANG PENERAPAN PERMAINAN FUTSAL SEBAGAI MEDIA EDUKASI KARAKTER PADA ANAK USIA DINI - Teguh Andibowo; Danang Adhi Kusuma; Muhammad Ilham Dewanto; Muhammad Ilham Saputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this research is to examine how futsal games affect the character development of early childhood children at PAUD and TK Nurul Iman Karanganyar. This study was conducted using a mixed-methods approach, which involved the use of observation and interviews in addition to a one-group pretest-posttest experimental design. There were 30 children aged 5–8 years who were the subjects of the study. They attended futsal classes for six months and practiced twice a week. Qualitative data were obtained through observations and interviews with teachers and parents, while quantitative data were obtained through character questionnaires measuring elements of discipline, cooperation, responsibility, sportsmanship, and leadership. Quantitative data analysis used paired sample t-tests, while qualitative data analysis used thematic analysis. The research results show a significant difference between the pretest and posttest scores in the futsal program and all character indicators, with an average increase of 36.4%. Interview and observation results also indicate that children have become more disciplined, cooperative, responsible, athletic, and more confident in class. The results show that futsal is an effective tool for teaching character to early childhood through enjoyable and meaningful play activities. According to this research, futsal can be included as one of the strategies for teaching character in early childhood education and kindergarten.